2012
DOI: 10.4236/ojas.2012.23028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of slow freezing and vitrification methods for Venda cockerel’s spermatozoa

Abstract: An improvement in avian semen cryopreservation is essential and has the potential to improve the cryo-gene banking efficiency. This study compared two cryopreservation methods (slow freezing and vitrification) and the effect of different thawing/warming temperatures (5˚C, 25˚C and 41˚C) on Venda cockerel's spermatozoa. Semen samples from Venda cockerels were diluted with modified Kobidil + extender supplemented with 8% dimethyl sulfoxide. Semen from each ejaculate was stained with nigrosin/eosin for viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…This was illustrated by a higher percentage of motile spermatozoa and viable spermatozoa with intact acrosomes and active mitochondria. This scenario agrees with previous studies that have reported better outcomes when sperm was preserved by slow freezing compared with those subjected to rapid cooling rates, as observed in several species, including turkeys (Meleagaris gallopavo), sandhill cranes (Grus canadensis), and roosters (Gallus gallus domesticus) [14,16]. Ultrarapid freezing in pellets might produce intracellular vitrification by drastically accelerating the cooling process, preventing the formation of intracellular ice crystals that can damage cells during the freezing/thawing process.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was illustrated by a higher percentage of motile spermatozoa and viable spermatozoa with intact acrosomes and active mitochondria. This scenario agrees with previous studies that have reported better outcomes when sperm was preserved by slow freezing compared with those subjected to rapid cooling rates, as observed in several species, including turkeys (Meleagaris gallopavo), sandhill cranes (Grus canadensis), and roosters (Gallus gallus domesticus) [14,16]. Ultrarapid freezing in pellets might produce intracellular vitrification by drastically accelerating the cooling process, preventing the formation of intracellular ice crystals that can damage cells during the freezing/thawing process.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with the study by Santiago-Moreno et al [19], in which the thawing conditions had no influence on sperm quality in the gentoo penguin (Pygoscelis papua). However, in other species, such as black-footed penguins (Spheniscus demersus) and roosters, higher thawing temperatures had a more detrimental effect on spermatozoa [14,19,20]. Therefore, it seems that the thawing temperature may affect sperm quality characteristics in a species-specific manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In slow freezing, the temperature is gradually reduced in a stepwise manner during cryopreservation process (Mphaphathi, Luseba, Sutherland, & Nedambale, 2012). The procedure was carried out as described by Tarig et al (2017).…”
Section: Slow Freezingmentioning
confidence: 99%
“…The rapid freezing or vitrification involves a swift speed of temperature conduction which provides a significant increase in cooling rate (Mphaphathi et al, 2012). The procedure consisting of different cryoprotectants was carried out on semen samples diluted with fraction 1 solution for the respective treatments as described by Srirattana et al (2013) with some modifications.…”
Section: Rapid Freezingmentioning
confidence: 99%